(untitled) (BIRDEM Medical Journal, 2023)
Background: Dementia is a clinical syndrome with loss of cognitive function, thinking, remembering and reasoning. It also affects the behavioral abilities to such an extent that interfere one’s daily life and activities. Alzheimer’s disease is known as the most common form of dementia frequently affecting people with 65 years or more. Abnormal glycemic status carries a significant role for developing dementia in elderly individuals. The aim of this study was to assess the glycemic status of diabetic population suffering from dementia. Methods: This cross-sectional study was done in the Department of Biochemistry and Molecular Biology, BIRDEM General Hospital from July 2018 to June 2019. According to inclusion criteria, after taking informed written consent from 222 respondents and their caregivers, a structured questionnaire (Addenbroke’s Cognitive Examination-ACE-III) was filled up for each subject to predict their ACE-III score. According to ACE-III score, the total study population were divided into two groups, as Group I- DM with Dementia (ACE-III score d” 70) and Group II- DM without Dementia (ACE-III score >70). Relevant biochemical parameters such as fasting and 2-hours after breakfast blood sugar and HbA1c level were measured by appropriate method. Statistical analysis was done with the help of SPSS software. Results: In this study, the differences between glycemic parameters (FBS 7.34± 1.86 mmol/L vs 6.52± 1.25 mmol/L, p <0.01, 2hrs ABF 11.94± 3.07 mmol/L vs 9.21±1.37 mmol/L, p <0.001 and HbA1c 8.80± 2.18% vs 6.41±0.64%, p < 0.001) between two groups were significant. A positive correlation of glycemic parameters were also found with dementia. Conclusion: This study concluded that glycaemic status was poor in diabetic patients with dementia than those without dementia. BIRDEM Med J 2023; 13(2): 76-80